2017
DOI: 10.3847/1538-3881/aa8c7c
|View full text |Cite
|
Sign up to set email alerts
|

The Scattering Outcomes of Kepler Circumbinary Planets: Planet Mass Ratio

Abstract: Recent studies reveal that the free eccentricities of are much larger than their forced eccentricities, implying that the scattering events may take place in their formation. The observed orbital configuration of Kepler-34b cannot be well reproduced in disk-driven migration models, whereas a two-planet scattering scenario can play a significant role of shaping the planetary configuration. These studies indicate that circumbinary planets discovered by Kepler may have experienced scattering process. In this wor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 51 publications
3
9
0
1
Order By: Relevance
“…A clear result of our multi-planet circumbinary system dynamical stability simulations is that at least one planet is ejected from the system with this result occurring in 87% -95% of simulations, a value broadly consistent with the results of previous studies of planet-planet scattering in circumbinary systems (e.g. Sutherland & Fabrycky 2016;Smullen et al 2016;Gong & Ji 2017;Gong 2017).…”
Section: Multiplanet Circumbinary Systemsupporting
confidence: 90%
See 2 more Smart Citations
“…A clear result of our multi-planet circumbinary system dynamical stability simulations is that at least one planet is ejected from the system with this result occurring in 87% -95% of simulations, a value broadly consistent with the results of previous studies of planet-planet scattering in circumbinary systems (e.g. Sutherland & Fabrycky 2016;Smullen et al 2016;Gong & Ji 2017;Gong 2017).…”
Section: Multiplanet Circumbinary Systemsupporting
confidence: 90%
“…Several previous studies have examined the impact of binary-planet and/or planetplanet scattering in circumbinary systems (e.g. Kratter & Shannon 2014;Smullen et al 2016;Sutherland & Fabrycky 2016;Gong & Ji 2017;Gong 2017).…”
Section: N-body Simulations Of Circumbinary Planetarymentioning
confidence: 99%
See 1 more Smart Citation
“…The SMA of CBP found by Kepler is distributed between 1.1 ac and 7.4 ac. Actually, most of them cluster at the vicinity of the unstable boundary of the binary (∼ 1.1 ac) (Gong & Ji 2017). It is generally believed that CBP formed in the outer region of the CBD and then migrated to their current location (Thun & Kley 2018).…”
Section: Model and Methodsmentioning
confidence: 99%
“…Along with the dissipation of gas disk, the eccentricities of planets can be further stirred up, subsequently the planet-planet scattering will ensue. Gong & Ji (2017) showed that the currently discovered circumbinary planets are more likely to be products of the scattering of multiplanetary systems. Smullen, Kratter & Shannon (2016) explored the scattering of multiple circumbinary planets and found that the planet-planet scattering in proximity to binaries leads to more ejections of planets than planet-planet or planet-star collisions in comparison with planet-planet scattering in single star systems.…”
Section: Introductionmentioning
confidence: 99%